2015
DOI: 10.1681/asn.2014030287
|View full text |Cite
|
Sign up to set email alerts
|

The Two Kidney to One Kidney Transition and Transplant Glomerulopathy

Abstract: The attrition rate of functioning allografts beyond the first year has not improved despite improved immunosuppression, suggesting that nonimmune mechanisms could be involved. Notably, glomerulopathies may account for about 40% of failed kidney allografts beyond the first year of engraftment, and glomerulosclerosis and progression to ESRD are caused by podocyte depletion. Model systems demonstrate that nephrectomy can precipitate hypertrophic podocyte stress that triggers progressive podocyte depletion leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
95
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 42 publications
11
95
2
Order By: Relevance
“…Podocytes, with their complex structure that includes foot processes and slit diaphragms, are a vital element of the glomerular filtration barrier to protein. Not surprisingly, Yang et al 9 found that transplantation of a single kidney resulted in an approximately 20% increase in glomerular volume and podocyte volume by 3 months posttransplantation, with a similar, corresponding decrease in podocyte nuclear density within glomeruli. However, somewhat surprisingly, they found that although the transplant patients had only a single functioning kidney, their urinary podocin/creatinine ratio (UPod/Cr; an estimate of podocyte excretion) at 3 months post-transplantation was on average approximately 6-fold higher than that of control patients with two kidneys and normal renal function, and this remained elevated beyond 5 years post-transplantation.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Podocytes, with their complex structure that includes foot processes and slit diaphragms, are a vital element of the glomerular filtration barrier to protein. Not surprisingly, Yang et al 9 found that transplantation of a single kidney resulted in an approximately 20% increase in glomerular volume and podocyte volume by 3 months posttransplantation, with a similar, corresponding decrease in podocyte nuclear density within glomeruli. However, somewhat surprisingly, they found that although the transplant patients had only a single functioning kidney, their urinary podocin/creatinine ratio (UPod/Cr; an estimate of podocyte excretion) at 3 months post-transplantation was on average approximately 6-fold higher than that of control patients with two kidneys and normal renal function, and this remained elevated beyond 5 years post-transplantation.…”
mentioning
confidence: 94%
“…However, somewhat surprisingly, they found that although the transplant patients had only a single functioning kidney, their urinary podocin/creatinine ratio (UPod/Cr; an estimate of podocyte excretion) at 3 months post-transplantation was on average approximately 6-fold higher than that of control patients with two kidneys and normal renal function, and this remained elevated beyond 5 years post-transplantation. Yang et al 9 also found that although acute rejection (mainly TCMR), acute tubular injury, calcineurin inhibitor toxicity, and BK virus nephropathy were not associated with a significant increase in UPod/Cr above levels seen in transplant recipients with biopsies showing no histologic lesions, TG was associated with an additional 5-to 10-fold increase in UPod/Cr, signifying a marked acceleration of podocyte detachment from GBMs.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…4,5 Recent studies determining absolute podocyte numbers and density also show in humans that, should any regenerative mechanism for podocytes exist within the glomerulus, it cannot be very effective. 6 …”
Section: Search For Intrinsic Progenitor Cells Within the Kidneymentioning
confidence: 99%